IDENTIFIKASI JENIS-JENIS BURUNG DI DESA WUASA KECAMATAN LORE UTARA KABUPATEN POSO - Laheping, Eko Prasetyo; Ningsih, Sri; Sustri, . (Jurnal Warta Rimba, 2018)
Indonesia is a tropical country and it has diversity of plants and animals which has 1 % of the land area of the world's land. Indonesia has about 325,000 living creatures that represent more than 16% of the world's living creatures. So far, Indonesia occupies second only from Brazil in terms of biological riches. Sulawesi mainland supports 396 species of settler and visitor type, which consist of land and freshwater birds, where 97 kinds which are endemics, and the largest number of endemic birds present in National Park of Lore Lindu. This study aimed to determine the type composition, diversity index, species dominance, species attendance rate, evenness diversity index, in Wuasa village, north Lore sub district, Poso district In National Park area of Lore Lindu. The usefulness of this research is to be used as an information material about the diversity of bird species in Wuasa village, north Lore sub district, Poso district In National Park area of Lore Lindu. The data collection method used was path transect that was a method used where the observer walked by following the direction and location of the transect line slowly and at the same time recording all bird species encountered. In this recording, besides it was done to the calculation of the number of types, it also noted the number of individuals of each species found. Based on research results in National Park of Lore Lindu in Wuasa village, north Lore sub district, Poso district, it found 52 birds species with a population of 234 individuals in primary forest 118 individuals and in secondary forest 114 individuals. From 52 species of birds, there were 23 species of birds being endemic of Sulawesi that were Snake Eagle of Sulawesi (Spilornis Rufipectus), Alap Eagle with the tail of the bottle (Accipiter trinotatus), Sulawesi Eagle (Spizaetus lanceolatus), Green yellow perkici (Trichoglossus flavoviridis), Kring-kring hill (Prioniturus platurus), Sulawesi Serindit (Loriculus stigmatus), the red beak serindit (Loriculus exilis), Sulawesi cirik-cirik (Meropogon forsteni), Sulawesi Julang (Rhyticeros cassidix), Sulawesi Caladi (Dendrocopos temminckii), Sulawesi’s grey woodpacker (Mulleripicus fulvus), Blue purple shrimp (Coracina temminckii), A dwarf purple shrimp (Coracina abboti), Sulawesi Srigunting (Dicrurus montanus), Sulawesi Pelanduk (Trichastoma celebense) Sulawesi Kipasan (Rhipidura teysmanni), Purple seam (Coracornis raveni), Yellow stomach ache (Pachycephala sullfuriventer), Eyebrows Jalak (Enodes erythrophris), the red flag Jalak (Scissirostrum dubium), the yellow pelvis chili (Dicaeum aureolimbatum), Sulawi chili (Dicaeum nerhkorni), the gray pelvis chili (Dicaeum celebicum). Key words : Sulawesi, Wuasa, Endemic, Bird.